2000
DOI: 10.1177/136346150003700102
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among the Cree of James Bay

Abstract: The object of this study was to identify potential risk and protective factors associated with psychological distress among the Cree of James Bay, through a secondary analysis of data on 1136 Cree (aged 15-85) from a random general population health survey in 1991. In multiple linear distress in the past week included: younger age, female gender, early loss of a parent or close relative, more life events in the year before the survey, a Downloaded from serious illness or drinking problem in the past year, ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…This is consistent with literature that suggests that family (both immediate and extended) and community are central aspects of Aboriginal lifestyle and identity (Castellano, 2002;Chandler & Lalonde, 1998). Also indicative of the importance of social support to well-being: In a study of psychological distress on the James Bay Cree, Kirmayer et al (2000) found that having fewer than five close friends was significantly associated with a higher level of psychological distress.…”
Section: Social Supportsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with literature that suggests that family (both immediate and extended) and community are central aspects of Aboriginal lifestyle and identity (Castellano, 2002;Chandler & Lalonde, 1998). Also indicative of the importance of social support to well-being: In a study of psychological distress on the James Bay Cree, Kirmayer et al (2000) found that having fewer than five close friends was significantly associated with a higher level of psychological distress.…”
Section: Social Supportsupporting
confidence: 88%
“…Below, we refer specifically to Chandler and Lalonde (1998), who looked at suicide rates among Aboriginal groups in British Columbia; Kirmayer, Boothroyd, Tanner, Adelson, and Robinson (2000), who examined the determinants of psychological distress among the Cree of James Bay using an index created by Santé Québec; Whitbeck, McMorris, Hoyt, Stubben, and LaFromboise (2002), who looked at depressive symptoms among American Indians in the upper Midwest; and Wingert (2010), who used the Community Well-Being Index and individual scores on the Psychological Well-Being Manifestation Scale as indicators of well-being.…”
Section: Aboriginal Peoples In Canadamentioning
confidence: 99%
“…26,27 The relationship between gender, depression and related symptomatology is likely a result of a complex interplay of social, economic, psychological and biological factors, including gender-role-related differences in help-seeking behaviour and expressions of distress. 28 Indigenous women's social and economic disadvantage relative to Indigenous men has been recognized and causally linked to the denigration of gender-egalitarian Indigenous culture following colonization.…”
Section: 25mentioning
confidence: 99%
“…Scores range from a minimum of 0 to a maximum of 100. Internal consistency of the scale within Cree respondents was found to be satisfactory (Cronbach's a 5 0?94) (34) . As in the 1987 Santé-Québec master survey (40) , a high level of PD was defined by any score above the 80th percentile of the index distribution observed in the Cree.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…n-3 LC PUFA may also exert other influences on brain biochemistry, such as membrane structure and fluidity; enzyme, receptor, ion channel, second messenger and blood-brain barrier functions; and increase cerebral blood flow (20,32,33) . Different risk and protective factors of mental health have been identified among the James Bay Cree (34) . However, the role of their traditional diet has received scant attention with regard to mental health.…”
mentioning
confidence: 99%